ANALISIS REAKSI BERANTAI PADA TAHAP PROSES PENGELASAN DI PT MULTIFAB - Wisnubroto, Petrus; Asih, Endang Widuri; Gunawan, Indra (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2010)
MULTIFAB is a company engaged in the field of technical companies highly specialist themselves in the field of production, fabrication equipment and specialized structures used in the chemical industry, petrochemical and oil and gas. In the normal process of production, especially in the welding process, its output is still a lot of experience of disability. Efforts to increase product quality and prevent and minimize product failure, this requires an analysis of quality control that is with a chain reaction analysis. From the data processing, as an early stage concept identifiers use problem FMEA, failure indicates that the effects of the highest-rated Slag Inclusion Risk Priority Number (RPN) at 256. Stage of quality improvement can be made using the method of Kaizen Kaizen is the Five-Step Plan and the 5W 1H. Chain reaction from the results of quality improvement. This is done by measuring the productivity of labor performed before and after improvement of quality. From the measurement of productivity, an increase of 0.01 and calculating the cost of reworks the calculation result of Rp 880 956. Based on the results of processing data on improved quality, causing a chain reaction that is after improved quality, productivity will increase and production costs willdecrease because the repair of products will be reduced.